Developmental Psychopathology 2016
DOI: 10.1002/9781119125556.devpsy411
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and Developmental Psychopathology

Abstract: Extensive theoretical and empirical work has outlined the importance of temperament in developmental psychopathology. This chapter focuses on recent advances in the conceptualization and measurement of temperament, including the progress that has been made in empirical work that has enabled researchers to test several proposed models of psychopathology. We first introduce the concept of temperament and discuss a series of agreed‐on principles. The next section includes consideration of the structure of tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
82
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(90 citation statements)
references
References 510 publications
6
82
1
1
Order By: Relevance
“…Surgency/Extraversion is identified by high vocal reactivity, engaging with rather than withdrawing from novelty, impulsivity, and strong positive affect (Stifter & Dollar, 2016). Orienting/regulation is identified by the ability to focus attention and regulate behavior and is a developmental precursor to effortful control that first emerges in toddlerhood.…”
Section: Rothbart's Conceptualizations Of Temperamentmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgency/Extraversion is identified by high vocal reactivity, engaging with rather than withdrawing from novelty, impulsivity, and strong positive affect (Stifter & Dollar, 2016). Orienting/regulation is identified by the ability to focus attention and regulate behavior and is a developmental precursor to effortful control that first emerges in toddlerhood.…”
Section: Rothbart's Conceptualizations Of Temperamentmentioning
confidence: 99%
“…Orienting/regulation is identified by the ability to focus attention and regulate behavior and is a developmental precursor to effortful control that first emerges in toddlerhood. Finally, negative affectivity is identified by sadness, fear, anger, distress to limitations, and reduced ability to soothe (Shiner et al, 2012; Stifter & Dollar, 2016). All three of these factors were examined in the present study as potential moderators of relations between mothers' bedtime EA with infants and security of infant-mother attachment at 12 months.…”
Section: Rothbart's Conceptualizations Of Temperamentmentioning
confidence: 99%
“…Temperament theory and research are often considered a promising avenue for understanding pathways toward children’s psychological and social adjustment by highlighting that variation in children’s temperament influences the processes that support or hinder adaptive developmental trajectories (Stifter & Dollar, 2016). Temperament is commonly conceptualized as reflecting constitutionally-based, relatively stable individual differences in reactivity and regulation within the realms of affect, activity, and attention (Goldsmith et al, 1987).…”
mentioning
confidence: 99%
“…Although inhibited and exuberant children are at risk for maladjustment, not all of these children go on to develop later difficulties (Stifter & Dollar, 2016). In fact, studies have revealed only a modest association between behavioral inhibition and internalizing behaviors and social withdrawal, including some studies that do not find this relation (Schwartz, Snidman, & Kagan, 1996; Stifter et al, 2008).…”
mentioning
confidence: 99%
“…This developmental pathway may account for most individuals who engage in lifelong delinquent behavior" [9]. Second, this finding receives impressive support from the research that strongly links impairments in self-control --which can be broadly defined as the ability to flexibly control/ regulate attention, behavior, and emotion in the service of valued goals and standards --to juvenile and adult criminal behavior [15,16]. Indeed, self-control may be the single most important variable in explaining developmental origins of antisocial behavior [17,18].…”
Section: Attention-deficit/ Hyperactivity Disordermentioning
confidence: 89%